PERSEPSI MAHASISWA UNUD TENTANG PARODI POLITIK NURHADI-ALDO DALAM PEMILU SERENTAK 2019 - Kirma Sihite, Ricky Aries; Suka Arjawa, I Gusti Putu Bagus; Kamajaya, Gede (JURNAL ILMIAH SOSIOLOGI (SOROT), 2021)
This research focuses on the perceptions of Udayana University students in the political parody of Nurhadi-Aldo's meme posts in the background during the simultaneous elections in 2019. The type of research used in this research is qualitative research with descriptive and explorative types. The theory used in this research is Arthur Asa Berger's semiotic theory which is a reference for analyzing the signs and meanings that exist in Nurhadi-Aldo's meme posts. The purpose of this study is to describe and explain the perceptions of Udayana University students in seeing the meanings and signs in Nurhadi Aldo's posts and the things that encourage students to follow the Nurhadi-Aldo phenomenon. The results showed that Udayana students saw fictional campaigns and funny memes displayed on Nurhadi-Aldo's social media accounts which made Udayana students interested in participating so that they had different responses. Keywords: Perception, Nurhadi-Aldo, Semiotics